2010
DOI: 10.1007/s12559-010-9061-4
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movements Show Optimal Average Anticipation with Natural Dynamic Scenes

Abstract: A less studied component of gaze allocation in dynamic real-world scenes is the time lag of eye movements in responding to dynamic attention-capturing events. Despite the vast amount of research on anticipatory gaze behaviour in natural situations, such as action execution and observation, little is known about the predictive nature of eye movements when viewing different types of natural or realistic scene sequences. In the present study, we quantify the degree of anticipation during the free viewing of dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
(39 reference statements)
2
19
0
Order By: Relevance
“…no offset needs to be taken into account. 20 The energy profiles of the attended and non-attended locations are computed on an anisotropic Laplacian pyramid decomposition of the videos (the pyramid having S = 5 spatial and T = 4 temporal levels), in a 5 by 5 degree spatial neighbourhood on all scales (which corresponds to 128×128 pixels on the highest spatial levels). In the periphery, the highest spatial and temporal frequency information is known to contribute little to attentional selection, since high spatio-temporal frequency is discernible only near the fovea.…”
Section: Learning the Contrast Modification Rulesmentioning
confidence: 99%
“…no offset needs to be taken into account. 20 The energy profiles of the attended and non-attended locations are computed on an anisotropic Laplacian pyramid decomposition of the videos (the pyramid having S = 5 spatial and T = 4 temporal levels), in a 5 by 5 degree spatial neighbourhood on all scales (which corresponds to 128×128 pixels on the highest spatial levels). In the periphery, the highest spatial and temporal frequency information is known to contribute little to attentional selection, since high spatio-temporal frequency is discernible only near the fovea.…”
Section: Learning the Contrast Modification Rulesmentioning
confidence: 99%
“…Attentional synchrony decreases over repeated presentation of the same videos (Dorr et al, 2010) and over prolonged presentation of the same dynamic scene (Carmi & Itti, 2006a;Dorr et al, 2010;Mital et al, 2011), suggesting that increasing familiarity and memory for scene content leads to divergent gaze behavior. Recent evidence of optimal anticipation of moments of high salience in dynamic scenes suggests that viewers formulate and act on predictions about the future of visual events (Vig, Dorr, Martinetz, & Barth, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, we have previously shown that the typical reaction time is stimulus dependent, and in natural scenes this average lag is near zero (i.e. no offset needs to be considered) due to the highly predictive nature of salient real-world events [45].…”
Section: B Data Set Labellingmentioning
confidence: 96%